Zirconium-substituted cobalt ferrite nanoparticle supported n-doped reduced graphene oxide as an efficient bifunctional electrocatalyst for rechargeable Zn-air battery - Kashyap, Varchaswal; Kurungot, Sreekumar (ACS Catalysis, 2018)
Solvothermal synthesis of zirconium-substituted cobalt ferrite nanoparticles was accomplished by the introduction of zirconium (Zr) in the spinel matrix to obtain a cost-effective and robust electrocatalyst that does not use noble metals. A variation in the cobalt ferrite structure CoFe2−xZrxO4 with Zr (0.1−0.4) substitution has significantly altered the overpotential for the electrocatalytic oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), leading to an optimum composition of CFZr(0.3). The incorporation of the foreign Zr4+ ion in the cobalt ferrite spinel lattices has effectively enhanced the oxygen evolution reaction (OER) activity in comparison to the parent cobalt ferrite (CF) nanocrystals. However, a nominal change in the ORR current density has been observed due to Zr incorporation. For the OER, the Zr-substituted catalyst has shown a 40 mV negative shift in the overpotential in comparison with the CF nanoparticles at 10 mA/cm2 current density. Interestingly, the in situ grafting of Zr-substituted cobalt ferrite nanoparticles over N-doped reduced graphene oxide (CFZr(0.3)/N-rGO) results in remarkably enhanced performance during the ORR and moderately favored the OER with an overall potential difference (ΔE) of 0.840 V. The enhanced bifunctional electrocatalytic activity of the material is crucial for the fabrication of high-performance rechargeable Zn−air batteries (ZABs). The prepared catalyst exhibited an overpotential of 80 mV for the ORR in comparison with the state-of-the-art (Pt/C) catalyst and an overpotential of 340 mV at 10 mA/cm2 current density for the OER from the standard value (1.23 V vs RHE). This potential bifunctional electrocatalyst has been employed as an electrode material for the fabrication of a primary ZAB, where it exhibited discharge capacities of 727 and 730 mAh/g at current densities of 20 and 30 mA/cm2 , respectively, under ambient conditions. The notable performance of the catalyst as a bifunctional material is observed during the cycling of the rechargeable ZAB. The prepared catalyst showed an increase of 200 mV in the overall operating overpotential after cycling for 10 cycles at 15 mA/cm2 in comparison to the 350 mV increase shown by the Pt/C catalyst.
Keywords: N-doped reduced graphene oxide; Oxygen Evolution Reaction; oxygen reduction reaction; zirconium-substituted cobalt ferrite